Rethinking teaching and learning at one university of technology in the context of the knowledge economy: A theoretical perspective - Moloi, Kholeka C; Isabirye, Anthony K; Lebelo, Ramoshweu S (International Journal of Innovative Research and Scientific Studies, 2025)
This research explores the imperative of rethinking teaching and learning at a university of technology in South Africa within the context of the burgeoning knowledge economy. Employing a literature-based methodology, the study delves into the concept of the knowledge economy, highlighting its defining characteristics and implications for educational practices. The exploration reveals significant challenges inherent in traditional learning and teaching paradigms that may inhibit effective student participation in a rapidly evolving economic landscape. The study argues that for students to navigate and contribute to the knowledge economy, there is a critical need to reformulate and innovate teaching and learning practices. This study identifies these challenges and offers future directions and recommendations, fostering a more adaptive, relevant, and effective educational framework. By addressing these issues, the research serves as a foundational step towards aligning educational outcomes with the demands of the knowledge economy, ultimately enhancing student engagement and employability in an increasingly competitive environment.